Host preference of Araecerus fasciculatus (DeGeer) (Coleoptera: Anthribidae): Adult presence and oviposition on twelve maize varieties: Preferensi inang Araecerus fasciculatus (DeGeer) (Coleoptera: Anthribidae): Kehadiran imago dan oviposisi pada dua belas varietas jagung - Khatami, Ammar Bielbark; Astuti, Ludji Pantja; Rizali, Akhmad (Jurnal Entomologi Indonesia, 2025)
The coffee bean weevil, Araecerus fasciculatus (DeGeer) (Coleoptera: Anthribidae), is a significant polyphagous stored product pest known to cause severe damage, including perforation and hollowing, in stored maize. This study aimed to determine the adult presence and oviposition preference of A. fasciculatus across twelve commercial maize varieties, and to analyze the correlation between preference and specific grain characteristics. The free choice test method (FCTM) was employed using preference cages with 12 or 6 chambers. In each test, 30 g of maize were infested with 60 pairs of 7- to 14-day-old A. fasciculatus adults for seven days. Adult presence (total and by sex) was recorded daily, and the number of eggs laid was counted microscopically at the end of the infestation period. The composition of maize varieties significantly affected adult presence and oviposition. Results consistently showed that the Pertiwi 3 variety was the most highly preferred for both adult presence (21.86 individuals in the 12-variety test) and oviposition (22.75 eggs in the 12-variety test). This high preference was supported by the Perkasa variety (e.g., 13.54 adults), which was also consistently preferred across the different test compositions. Further analysis using the generalized linear model (GLM) indicated that the preference is driven by grain quality: adult presence showed a positive correlation with moisture content, while oviposition exhibited a negative correlation with phenol content. These findings suggest that the Pertiwi 3 variety, likely due to its favorable physical attributes and low levels of chemical defense, is the most susceptible to A. fasciculatus infestation.